The electronic structure, optical absorption and photocatalytic water splitting of (Fe + Ni)-codoped TiO2: A DFT + U study. (23rd February 2017) - Lin, Yanming; Jiang, Zhenyi; Zhu, Chaoyuan; Zhang, Ruiqin; Hu, Xiaoyun; Zhang, Xiaodong; Zhu, Haiyan; Lin, Sheng Hsien
Abstract: The electronic and optical properties of Fe or/and Ni (co)doped anatase and rutile TiO2 were investigated using the spin-polarized density functional theory. Our calculated results indicate that the synergistic effect of (Fe + Ni) codoping can lead to a band gap narrowing and the hybridized states of Fe 3 d and Ni 3 d appearing in the forbidden gap, which enhances greatly the optical absorption of TiO2 nanomaterials from the ultraviolet-light to the infrared-light region and reduces the recombination of photogenerated electron–hole pairs. In particular, (Fe + Ni) codoping can improve greatly the infrared-light absorption of TiO2 nanomaterials. Furthermore, the researches of electronegativity show that (Fe + Ni)-codoped TiO2 system has a stronger redox power for hydrogen generation by photocatalytic water splitting compared with pure, Fe-doped, and Ni-doped TiO2 systems. These results lead to an outstanding solar energy photocatalytic water splitting for hydrogen generation in (Fe + Ni)-codoped TiO2 photocatalyst. Highlights: Hybridized of Fe 3 d and Ni 3 d state reduces the recombination of electron–hole pairs. Synergistic effect of (Fe + Ni) codoping enhances an infrared-light absorption of TiO2 . (Fe + Ni)-codoped TiO2 has a stronger redox power for photocatalytic water splitting. Our calculated results provide a possible explanation for experimental observations.